Student Academic Success: Can it be Improved Through the Discipline of Learning? - Budiwati, Neti; Rosalina, Cindy; Hasan, Muhammad; Dewi, Retno Mustika; Geminastiti H, Kinanti (Journal of Ecohumanism, 2024)
This research aims to determine the influence of learning discipline on students' academic success with peers as a moderator variable. The method used is an explanatory survey with questionnaire as data collection techniques. The populations in this study were all 643 students. Using simple random sampling techniques, a sample of 254 students was obtained. Data analysis uses multiple regression analysis with Moderate Regression Analysis (MRA). The results show that student academic success is influenced by the level of discipline; and peers moderate the influence of learning discipline on student academic success. These findings imply that improving student academic success can be improved through increasing learning discipline and supportive peers.